The prevalence of wide QRS complex (≥110 ms) among the population, depending on sex, age and place of residence - G. A. Muromtseva; V. G. Vilkov; S. A. Shalnova; V. V. Konstantinov; A. D. Deev; S. E. Evstifeeva; Yu. A. Balanova; A. E. Imaeva; A. V. Kapustina; N. S. Karamnova; E. V. Shlyakhto; S. A. Boytsov; et al. (Российский кардиологический журнал)
Aim. To assess the prevalence of wide QRS complex (≥110 ms) among the population, depending on sex, age, place of residence (urban or rural area), the presence of obesity and cardiovascular disease.Material and methods. The analysis was based on the ESSE-RF study (n=17,364, men — 38%). Twelve-lead resting electrocardiography (ECG) data from the regions participating in the study were analyzed according to the Minnesota code manual. Patients were divided into groups of QRS <110 ms and ≥110 ms (wide QRS).Results. QRS groups did not differ in heart rate and age. The prevalence of wide QRS complex in the population amounted to 17,2%. Men were likely to have wide QRS than women (18,5% and 16,2%, respectively, p<0,0005) due to the increased frequency of “preblock” QRS duration (110-119 ms; 12,3% vs 10,9%, respectively, p<0,025). The prevalence of QRS≥120 ms in the sex groups was the same, almost 7%. The prevalence of widened QRS in the population significantly exceeded other unfavorable prognostic ECG indicators, such as major ECG abnormalities, conduction disorders, abnormal Q wave (QS). The prevalence of wide QRS complex increased with age from 11,1% to 19,2, (p<0,001). The highest increase in prevalence of wide QRS complex was observed after 55 years; nondynamic periods were recorded in men from 25, and in women from 35 to 54 years. In contrast to women, the prevalence of wide QRS in men did not depend on the place of residence (18,6% in urban and 18,3% in rural areas); in rural women this parameter was observed as often as in men. This may indicate a more severe epidemiological situation of car - diovascular disease in rural residents. Obesity, high blood pressure, and a history of coronary artery disease were more common in the group of wide QRS complex.Conclusion. For wide QRS complex, the same age and sex relationships are cha - racteristic as for the basic routine ECG indicators. The prevalence of wide QRS in the population exceeds major ECG abnormalities, conduction disorders, abnormal Q wave (QS). In rural residents, the increased prevalence of wide QRS is probably due to the greater prevalence of obesity and hypertension.